S50 Understanding Heroin Overdose: A Study of the Acute Respiratory Depressant Effects of Injected Pharmaceutical Heroin. (12th November 2015) - Jolley, CJ; Bell, J; Rafferty, GF; Moxham, J; Strang, J
Abstract : Introduction and objectives: Opioids are respiratory depressants and heroin/opioid overdose is a major contributor to the excess mortality of heroin addicts. The individual and situational variability of respiratory depression caused by intravenous heroin is poorly understood. The aim of this study was to use advanced physiological monitoring to follow the time course and severity of acute opioid-induced respiratory depression. Methods: 10 patients (9/10 with chronic airflow obstruction) undergoing supervised injectable opioid treatment for heroin addiction received their usual prescribed dose of injectable opioid (diamorphine or methadone) (IOT), and their usual prescribed dose of oral opioid (methadone or sustained release oral morphine) after 30 min. The main outcome measures were pulse oximetry (SpO2 %), end-tidal CO2 % (ETCO2 %) and neural respiratory drive (NRD) (quantified using parasternal intercostal muscle electromyography). Significant respiratory depression was defined as absence of inspiratory airflow >10s, SpO2 % <90% for >10s and ETCO2 % per breath >6.5%. Results: ETCO2 % indicated significant respiratory depression following IOT in 8/10 patients, with levels increasing from baseline 4.7 (4.5 to 5.4)% to 5.4 (5.1 to 5.7)% at 30 min, p = 0.01. The median (range) peak ETCO2 % per breath was 6.9% (5.2 to 7.8). In contrast, SpO2 % indicated significant respiratory depression in only 4/10 patients, with small absolute changes in SpO2 % from 96.5 (95.1 to 99.2)% at baseline to 96.2 (95.2 to 97.0%) at 30 min. A non-significant decline in NRD from baseline (109.5 (69.5 to 185.1) a.u.) to 30 min post IOT 84.3 (59.2 to 118.1) a.u., p = 0.12) was also observed. Baseline NRD and opioid-induced drop in SpO2 % were inversely related (r = -0.67, p = 0.04). Conclusion: Significant acute respiratory depression is commonly induced by opioid drugs prescribed to treat opioid addiction. Hypoventilation is reliably detected by capnography, but not by SpO2 % alone. Chronic suppression of NRD in the presence of underlying lung disease may be a risk factor for acute opioid-induced respiratory depression.